UNUSUAL TYPE OF NODULAR LUNG DISEASE IN RHEUMATOID ARTHRITIS: A RARE CASE - Irina V Liskina; N S Opanasenko; L M Zagaba; A V Tereshkovich (Научно-практическая ревматология)
The article presents a rare case of pulmonary manifestation of seropositive protracted rheumatoid arthritis in the form of bronchocentric granulomatosis. The algorithm for diagnosis is described in details in the context of the known literature on pulmonary manifestations as a complication of rheumatoid arthritis and morphology of bronchocentric granulomatosis.